Synovial sarcoma of the foot enlightening etiology: a case report - Yu, N.; Cheng, F.; Xiao et al., L. (Acta Biomedica Atenei Parmensis, 2011)
Synovial sarcoma which mainly affects the periarticular tissues of the extremities in young adults is an uncommon seen soft tissue sarcoma with uncertain causative factors. We report a long-course primary synovial sarcoma of the left foot in a 46-year-old man. The initial symptom occurred when he was 26-year-old. During these 20 years, he underwent two operations, with the diagnosis of synovial cyst and nodular synovitis. This time, a lobulated 7× 5.5 × 6 cm mass was found on computed tomography, and a final diagnosis of synovial sarcoma was made by histological study. The patient underwent a below knee amputation. We report this case aiming to discuss about the potential etiology of synovial sarcoma. Physicians should be aware of the possibility of this malignant mass.